PENGEMBANGAN MICRO MODUL MATA KULIAH PENGELOLAAN SUMBER DAYA BELAJAR INTERAKTIF DIGITAL PADA MAHASISWA TEKNOLOGI PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASAR - Risma Asmita; Abd. Haling; Farida Febriati (STKIP Subang, 2026)
The use of digital micro modules is very much needed in the learning process along with technological developments to improve the quality of learning, curriculum development, learning innovation, and improving the quality and completeness of facilities and infrastructure. This study aims to 1) determine the level of student needs for digital interactive micro modules for learning resource management, 2) determine the design of digital interactive micro modules for learning resource management, 3) determine the level of validity and practicality of digital interactive micro modules for learning resource management. This study uses a Research and Development (R&D) approach with the ADDIE development model which includes five stages: analysis, design, development, implementation, and evaluation. The study was conducted at the Educational Technology Study Program, Faculty of Education, Makassar State University. The subjects of this study were 2 validators, namely material expert & media expert validators, 21 students of the educational technology class, and 1 lecturer teaching the course. The results of content validation are in very good qualifications, the results of media validation are in very good qualifications. Practicality trials were conducted on two user targets, namely student responses are in very good qualifications and the responses of the lecturers teaching the course are in very good qualifications. Based on the results of the analysis, it can be concluded that the digital interactive micro module is valid and practical for use in the learning process in the Learning Resource Management Course.